Incremental Validity of Multi-Method and Multi-Informant Evaluations in the Clinical Diagnosis of Preschool ADHD. Issue 10 (August 2022) - Chen, I-Chun; Lee, Pai-Wei; Wang, Liang-Jen; Chang, Chih-Hao; Lin, Cheng-Hsiu; Ko, Li-Wei
Objectives: This study investigated the discriminative validity of various single or combined measurements of electroencephalogram (EEG) data, Conners' Kiddie Continuous Performance Test (K-CPT), and Disruptive Behavior Disorder Rating Scale (DBDRS) to differentiate preschool children with ADHD from those with typical development (TD). Method: We recruited 70 preschoolers, of whom 38 were diagnosed with ADHD and 32 exhibited TD; all participants underwent the K-CPT and wireless EEG recording in different conditions (rest, slow-rate, and fast-rate task). Results: Slow-rate task-related central parietal delta (1–4 Hz) and central alpha (8–13 Hz) and beta (13–30 Hz) powers between groups with ADHD and TD were significantly distinct ( p < .05). A combination of DBDRS, K-CPT, and specific EEG data provided the best probability scores (area under curve = 0.926, p < .001) and discriminative validity to identify preschool children with ADHD (overall correct classification rate = 85.71%). Conclusions: Multi-method and multi-informant evaluations should be emphasized in clinical diagnosis of preschool ADHD.